Comparative study on seed metering units for wet-direct seeding of rice - Guru, Prabhat Kumar; Shrivastava, Atul Kumar; Tiwari, Priyanka; Nagori, Ankur; Narwariya, Bhagwan Singh; Khandai, Suryakant (ORYZA-An International Journal of Rice, 2023)
In sowing operation, seed metering units plays a crucial role in achieving the optimal plant spacing, uniform crop emergence, crop yield, resource efficiency, and overall farm profitability. This research was conducted to access performance of four metering mechanisms (drum type, fluted roller type, inclined plate type-I, and inclined plate type-II) with three distinct paddy varieties (IR-64, JR-206, and Kranti) and at three levels of operating speed (1, 1.5 and 2 km/h). A test rig was developed for conducting the lab experiments to measure the seed rate and mechanical damage for all four metering units. Across all types of metering units and seed varieties, a trend was observed where the seed rate tends to decrease as the operating speed increases and mechanical damage to seeds increases with increase in operating speed. For drum type, fluted roller type, inclined plate type-I, inclined plate type-II metering unit seed rate varies from 21.67 to 27.91 kg/ha, 47.44 to 55.98 kg/ha, 26.5 to 30.09 kg/ha, and 28.98 to 33.23 Kg/ha whereas, seed damage ranged from 1.1 to 2.1%, 8.89 to 12.8 %,0.09 to 0.17 %, and 2.21 to 3.54 %, respectively. Among the metering units, the inclined plate type-I emerges as the preferred choice, showcasing minimal mechanical damage alongside optimum seed rate. These findings have important implications in selecting metering unit for wet-direct seeding method of rice cultivation, with the potential to enhance rice production and productivity.